Technical characteristics of the Nasta'liq line (Journal of the College of Basic Education, 2023)
The Nasta'liq script is one of the Arabic scripts commonly used by calligraphers in the Eastthe Islamic world since the 8th century AH 14 AD); And used in the line of the Koran and official correspondenceand personal. This font was distinguished by its beauty stemming from the balance of its letters, the flow of its extensions, and the clarityIn his writing. And nastaliq in the language is a carved term consisting of two words (copy and comment) and indicateThese two words are on two types of calligraphy: Naskh and Ta’liq, which were spread and known in the periodPrior to the emergence of the Nastaliq line in the east of the Islamic world. From here, historians differedAnd the Arab and foreign researchers who came in their studies to mention the Nasta'liq line on the originalFrom which this line was derived, some of them linked its origin to the Naskh line only; Some of them added a line to itThe commentary, and others agreed to call it the Persian script. Because they believe that this line was inventedIt originated and developed in Persia. From here came the interest in preparing this research, as the research presented a problemIt was researched with the following question: (What are the technical characteristics of the Nasta'liq calligraphy), as the research aims to revealAbout these characteristics of the Iranian, Turkish and Pakistani schools of the century (8 AH-41 AD) because they areThe period in which the commentary line flourished and developed. “As for the first chapter, it dealt with the theoretical frameworkExplaining the Ta'liq line and its origins, passing through the Nasta'liq line, in addition to its uses in copyingReligious and non-religious manuscripts. In the topic related to the characteristics of the Nasta'liq line, it was shownCharacteristics of letters for each school of Nastaliq calligraphy. As for the results of the search, it wascame out with:1. There were stylistic differences in the Nasta'liq calligraphy in terms of point measurement and shapeIt differs from one school to another.